PEMETAAN AREA DI PROVINSI JAWA BARAT INDONESIA BERDASARKAN FAKTOR-FAKTOR YANG BERKONTRIBUSI PADA KEJADIAN DEMAM BERDARAH DENGUE - Hendrawati, Triyani; Putri Samsi, Haana Lahanda; Munawwaroh, Ihksa (LPPM Universitas Bina Bangsa, 2024)
Dengue haemorrhagic fever (DHF) is endemic in major cities in Indonesia. West Java Province is one of the provinces in Indonesia with a high number of DHF cases every year. To minimise the spread and increase of DHF cases can be done by controlling the factors that influence it. This study aims to categorise cities/districts in West Java based on factors that influence DHF cases. The data used are population density (Soul/ ), proper sanitation (%), healthy and clean living behaviour (%), access to proper water sources (%), and health index (%) in 27 cities/districts in West Java in 2021. In this study, the method used is the Hierarchical clustering method; namely the single linkage method, the complete linkage method, the average linkage method, and the ward method. The clustering methods are then compared based on the value of their standard deviation. The analysis results show that the best method used is the complete linkage method. The results of clustering areas in West Java based on factors affecting dengue cases obtained three clusters. Cluster 1 is the cluster with the highest level of dengue cases compared to other clusters. Cluster 1 consists of Depok city, Bogor city, Cirebon city, Bandung city, and Cimahi city. The characteristic of cluster 1 is that it has the highest average population density compared to other clusters. Cluster 2 consists of Cirebon, Bekasi, Banjar City, Bogor, Bandung, Karawang, West Bandung, Purwakarta, Kuningan, Majalengka, Pangandaran, Indramayu, Garut, Ciamis, Subang, Sukabumi, Cianjur, Tasikmalaya, and Sumedang. Cluster 2 has the characteristics of having the highest average percentage of households with access to proper sanitation, percentage of households with clean and healthy behaviour, and health index. Cluster 3 is Sukabumi City and Tasikmalaya City. Cluster 3 has characteristics with the lowest average in the percentage of households that have access to proper sanitation and the percentage of households with clean and healthy behaviour.